Adult Rhabdomyosarcoma of the Maxillary Sinus with Orbital Extension. (August 2014) - Parikh, Deep; Spindle, Jordan; Linden, Craig; Bardarov, Svetoslav; Shinder, Roman
Abstract A 40-year-old male presented with 2 weeks of left facial pain, nasal congestion, dysphonia, and epistaxis along with left-sided epiphora. CT showed a large infiltrative mass centered in the left maxillary sinus with extension into the left orbit, bilateral paranasal sinuses, nasal cavity, and bilateral enlarged cervical lymph nodes. Biopsy results confirmed adult alveolar rhabdomyosarcoma (RMS). Systemic workup confirmed bilateral cervical lymph node metastasis. Currently the patient is undergoing chemotherapy. We describe a rare case of adult paranasal sinus RMS with orbital invasion.